Teachers’ quality and students’ breakfast intake as correlates of academic achievement in Junior Secondary School Mathematics in Lagos State, Nigeria - O. M. Alade; S. Aletan; M. R. Sokenu; B. S. Sokenu (African Journal of Behavioural and Scale Development Research, 2019)
This study investigated the relationship between teachers' quality and students' breakfast intake, and academic achievement in junior secondary school Mathematics in Lagos State. Stratified random sampling was used to select a sample of 720 junior secondary school II students from 3 Educational Districts of Lagos State. Four research questions guided the study. Data was collected using Questionnaire on students' breakfast intake (r=0.86), Students' Evaluation of Teacher's Quality Scale (r=0.78) and Mathematics Achievement Test (r=0.82).Data was analyzed by utilizing Product Moment correlation coefficient and multiple regressions analysis at 0.05 level of significance. The outcome showed a significant relationship between the indicator variables and academic achievement in Mathematics. Teachers' quality has a major role in predicting students' academic achievement in junior secondary school Mathematics in Lagos State. Recommendations were made for the improvement of the quality of teachers and regular in-take of breakfast by students to ensure improvement in students' academic achievement in Mathematics.